Site-Specific Conjugation for Fully Controlled Glycoconjugate Vaccine Preparation - Pillot, Aline; Defontaine, Alain; Fateh, Amina; Lambert, Annie; Prasanna, Maruthi; Fanuel, Mathieu; Pipelier, Muriel; Csaba, Noemi; Violo, Typhaine; Camberlein, Emilie; Grandjean, Cyrille (Frontiers in Chemistry, 2019)
Glycoconjugate vaccines are formed by covalently link a carbohydrate antigen to a carrier protein whose role is to achieve a long lasting immune response directed against the carbohydrate antigen. The nature of the sugar antigen, its length, its ratio per carrier protein and the conjugation chemistry impact on both structure and the immune response of a glycoconjugate vaccine. In addition it has long been assumed that the sites at which the carbohydrate antigen is attached can also have an impact. These important issue can now be addressed owing to the development of novel chemoselective ligation reactions as well as techniques such as site-selective mutagenesis, glycoengineering, or extension of the genetic code. The preparation and characterization of homogeneous bivalent pneumococcal vaccines is reported. The preparation and characterization of homogeneous bivalent pneumococcal vaccines is reported. A synthetic tetrasaccharide representative of the serotype 14 capsular polysaccharide of Streptococcus pneumoniae has been linked using the thiol/maleimide coupling chemistry to four different Pneumococcal surface adhesin A (PsaA) mutants, each harboring a single cysteine mutation at a defined position. Humoral response of these 1 to 1 carbohydrate antigen/PsaA conjugates have been assessed in mice. Our results showed that the carbohydrate antigen-PsaA connectivity impacts the anti-carrier response and raise questions about the design of glycoconjugate vaccine whereby the protein plays the dual role of immunogen and carrier.